The case of squamous cell carcinoma of the face treated with combined method - Żaba, Ryszard; Kaszewski, Sebastian; Michalewska, Agnieszka; Dudzińska, Agnieszka (Przewodnik Lekarza/Guide for GPs, 2005)
Squamous cell carcinoma (SCC) is the second most common type of skin cancer. Basal cell carcinoma is the most common. However, some argue that an actinic keratosis should be considered as an SCC that is superficial. The tumor typically appears as a papule or nodule, with varying degrees of hyperkeratosis and ulceration. The disease has been linked to immunosuppression, arsenic exposure, radiation, chronic ulceration, and human papillomavirus (HPV) infection. Excision, Mohs surgery, radiation, and electrosurgery are standard treatment for SCC. We report a case in which 5% imiquimod cream, immune response modifier with potent antiviral and antitumor activity, was effective in the management of SCC in 65 year old man.